1975
DOI: 10.1139/z75-177
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study of movements of harbor porpoises (Phocoena phocoena) in the Bay of Fundy using radiotelemetry

Abstract: Six harbor porpoises captured in herring weirs between September 1973 and September 1974 on the southern coast of New Brunswick were tagged and released. The three smallest animals were given visible dorsal fin tags, and the three larger specimens radiotelemetric packages attached to their dorsal fins. These animals were tracked using an ADFS-210 receiver coupled with a fixed-loop array on a 6.7-m mast antenna. Good signals were received at distances of up to 16 km using frequencies in the 26–28 MHz region. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1977
1977
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…In the first case, preliminary radiotelemetric tracking studies by Gaskin et al (1975) Can. J. Zool.…”
Section: -! mentioning
confidence: 96%
“…In the first case, preliminary radiotelemetric tracking studies by Gaskin et al (1975) Can. J. Zool.…”
Section: -! mentioning
confidence: 96%
“…Wursig andWursig (1979, 1980), also using theodolite tracking, found average swimming speeds of 6.1 km/h for bottlenose dolphins (Tursiops truncatus), and 7.7 km/h for dusky dolphins (La~enorhynchus obscurus) in the South Atlantic. Gaskin et al (1975), using radiotelemetry, found a mean swimming speed of about 2 km/h for slow surfacing harbor porpoises in the Bay of Fundy , New Brunswick. Loeb (1972) and Morejohn (1979) have interpreted slow rolling as sleeping or resting.…”
Section: Swimming Behaviormentioning
confidence: 99%
“…Although successful in determining short‐term movements of dolphins, many of these tags caused long‐term dorsal fin damage (Gaskin et al . , Irvine et al . ).…”
mentioning
confidence: 99%